PERANAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENINGKATKAN INTERAKSI PEMBELAJARAN DI SEKOLAH - Hairuddin Cikka (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
PAI teachers must have 5 competencies, namely pedagogic, personality, social professional and leadership in the learning interaction. A teacher must be able to build interactions with students because learning interactions are social activities between students and their peers, students and teachers in the form of social communication in the classroom or outside the classroom